Correlative Coordination and Variable Subject–Verb Agreement in German - Claudia Felser (Languages, 2021)
Coordinated subjects often show variable number agreement with the finite verb, but linguistic approaches to this phenomenon have rarely been informed by systematically collected data. We report the results from three experiments investigating German speakers’ agreement preferences with complex subjects joined by the correlative conjunctions sowohl…als auch (‘both…and’), weder…noch (‘neither…nor’) or entweder…oder (‘either…or’). We examine to what extent conjunction type and a conjunct’s relative proximity to the verb affect the acceptability and processibility of singular vs. plural agreement. Experiment 1 was an untimed acceptability rating task, Experiment 2 a timed sentence completion task, and Experiment 3 was a self-paced reading task. Taken together, our results show that number agreement with correlative coordination in German is primarily determined by a default constraint triggering plural agreement, which interacts with linear order and semantic factors. Semantic differences between conjunctions only affected speakers’ agreement preferences in the absence of processing pressure but not their initial agreement computation. The combined results from our offline and online experimental measures of German speakers’ agreement preferences suggest that the constraints under investigation do not only differ in their relative weighting but also in their relative timing during agreement computation.